2016
DOI: 10.3906/zoo-1510-64
|View full text |Cite
|
Sign up to set email alerts
|

Bird communities of different woody vegetation types from the Niraj Valley, Romania

Abstract: In this paper, the bird assemblages of different woody vegetation types are presented in a human-modified Eastern European landscape. The studied territory is part of a Special Protection Area for bird species. The following sampling areas were included in the study: hornbeam-beech, oak-hornbeam, and sessile oak forests; thickets of willow; forests of white willow; scrubs of blackthorn and hawthorn; and orchards. Birds were grouped in a community typical of deciduous forests and in another community typical of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The dependence of the diversity of bird communities on the heterogeneity of the stand and the mosaic of habitats was repeatedly emphasised in other studies (Tews et al, 2004;Giltena et al, 2007;Moreno-Rueda, Pizzaro, 2009;Stefanova, Salek, 2014;Domokos E., Domokos J., 2016). The authors suggested that the transformed environment could reduce species abundance because of a decrease in the populations of some species.…”
Section: Discussionmentioning
confidence: 97%
“…The dependence of the diversity of bird communities on the heterogeneity of the stand and the mosaic of habitats was repeatedly emphasised in other studies (Tews et al, 2004;Giltena et al, 2007;Moreno-Rueda, Pizzaro, 2009;Stefanova, Salek, 2014;Domokos E., Domokos J., 2016). The authors suggested that the transformed environment could reduce species abundance because of a decrease in the populations of some species.…”
Section: Discussionmentioning
confidence: 97%
“…The chaffinch (Fringilla coelebs Linnaeus, 1758) is a common insectivorous bird and a principal contributor to forest ecosystem communities of the temperate climate zone (Browne, 2004;Amar et al, 2006;Baillie et al, 2006;Domokos & Domokos, 2016;Ramdani et al, 2019). It is also a migrant of global conservation concern (Bern Convention) and studies on the foraging ecology of the species will defini-tely assist in its conservation.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a migrant of global conservation concern (Bern Convention) and studies on the foraging ecology of the species will defini-tely assist in its conservation. It has been already revealed that habitat conditions of the chaffinch are crucial for the successful breeding and stability of its population in forests of England (Whittingham et al, 2001;Macleod et al, 2004), Turkey, Germany (Bergen & Abs, 1997;Batary et al, 2014), Sweden (Felton et al, 2016), Romania (Domokos & Domokos, 2016), Spain (Moreno-Rueda & Pizarro, 2009;Peris & Montelongo, 2014) and North East Algeria (Ramdani et al, 2019). The role of artificial light and noise for the finches when they search for food has also been studied (Quinn et al, 2006;Kempenaers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These practices might have negative consequences for birds that depend on shrubs for breeding and foraging, which showed that it was possible to keep breeding species in managed forests as long as sufficient shrub layer was retained in the understory (Camprodon, Brotons, 2006;Heyman, 2010). The analysis of the ecological structure of the birds communities showed that forests are more abundant in species associated with closed forest habitats than other plant associations (Domokos E., Domokos J., 2016). Recent studies suggest that birds communities are influenced by woodland vegetation cover at both the patch and the landscape scales and that these relationships are consistent over time (Ikin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%